2013
DOI: 10.1155/2013/515792
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelastic Characteristics in Thermal Barrier Coatings with a Graded Layer between the Top and Bond Coats

Abstract: A graded layer was introduced at the interface between the top and bond coats to reduce the risk of failure in a thermal barrier coating (TBC) system, and the thermoelastic behavior was investigated through mathematical approaches. Two types of TBC model with and without the graded layer, subject to a symmetric temperature distribution in the longitudinal direction, were taken into consideration to evaluate thermoelastic behaviors such as temperature distribution, displacement, and thermal stress. Thermoelasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…They prepared a The composition-graded coating from 100% metal on the substrate to 100% ceramics on the top layer caused the interface between the two substances to disappear [141] while retaining the properties of a variety of composite materials. The composition-graded coatings improve the bond strength and toughness of the coating and reduce the thermal stress at the interface [142][143][144][145]. Saeedi et al [146] prepared a five-layer functionally graded APS-TBC by changing the composition of YSZ/NiCrAlY.…”
Section: Functionally Graded Ttbcsmentioning
confidence: 99%
“…They prepared a The composition-graded coating from 100% metal on the substrate to 100% ceramics on the top layer caused the interface between the two substances to disappear [141] while retaining the properties of a variety of composite materials. The composition-graded coatings improve the bond strength and toughness of the coating and reduce the thermal stress at the interface [142][143][144][145]. Saeedi et al [146] prepared a five-layer functionally graded APS-TBC by changing the composition of YSZ/NiCrAlY.…”
Section: Functionally Graded Ttbcsmentioning
confidence: 99%
“…As a consequence of such an architecture in functionally graded thermal barrier coatings, their physical and mechanical properties vary gradually across their coating thickness. Functionally graded thermal barrier coatings have improved thermal cycle lifetime and adhesion strength compared to conventional double-layer structures [ 12 , 14 , 15 , 16 , 17 , 18 ]. Kim et al [ 15 ] investigated thermoelastic characteristics in TBCs with a graded layer between the top coat and bond coat.…”
Section: Introductionmentioning
confidence: 99%
“…Functionally graded thermal barrier coatings have improved thermal cycle lifetime and adhesion strength compared to conventional double-layer structures [ 12 , 14 , 15 , 16 , 17 , 18 ]. Kim et al [ 15 ] investigated thermoelastic characteristics in TBCs with a graded layer between the top coat and bond coat. By using the finite element method (FEM), they identified that the functionally graded layer can considerably improve cycle lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the temperature decreases across TBCs at specific operation condition are governed by the material and geometrical properties of the TC layer, especially the thermal conductivity and thickness [3][4][5][6][7][8][9]. For a given ceramic material, the thermal insulation capability of the coatings enhances with the increase of TC thickness.…”
Section: Introductionmentioning
confidence: 99%